Iron - The missing nutritional link to performance - Gusmer, R. J.; Dengel, D. R. (Techniques Magazine, 2012)
Iron is a commonly overlooked and misunderstood nutritional element that plays a vital role in an athlete`s performance. Coaches can identify athletes who are iron-deficient through symptoms such as exhaustion and decreased work capacity by blood testing serum ferritin levels. Of highest importance is prevention of iron deficiency, which focuses on educating athletes to consume adequate dietary iron sources and supplementation when indicated. Practical recommendations include: • Serum ferritin levels below 35 ìg/L are suggested to be supplemented with 125-325 mg ferrous sulfate/day (Nielsen & Nachigall, 1998; Cowell et al., 2003; Eichner, 2001) • Iron should be consumed with Vitamin C and apart from calcium and caffeine (Ryan, 2004) • Iron testing should be done 3-4 times/year to determine the normal iron levels for each athlete and monitored consistently though seasons • Hemoglobin saturation levels used solely for diagnosis are not recommend due to hemodilution (Chatard et al., 1999) • Serum iron levels used solely are not recommended due to hourly variations (Worwood, 1997; Chatard et al., 1999) • Effects from iron toxicity can occur when serum ferritin >200 ìg/L and is uncommon for individuals indicated for iron deficiency (serum ferritin <35 ìg/L) (Ryan, 2004; Nielsen & Nachtigall, 1998) Conclusively, monitoring the iron status of athletes may be the missing nutritional link for optimal performance.